The impact of transformational leadership on the decision-making process in secondary schools in Tabuk - Albalawi, Fahad Aliyan (Journal of Educational and Psychological Sciences, 2023)
This study aimed to investigate the impact of transformational leadership on the decision-making process from the point of view of high school principals in Tabuk. To achieve the aim of the study, the researcher followed the descriptive analytical approach by applying the questionnaire to a random sample of (150) principals. The results of the study revealed that the degree of application of transformational leadership among secondary school principals in Tabuk was high, with an average of (3.97) and the degree of effectiveness of the decision-making process in Tabuk schools from the point of view of leaders and managers is also high, with an average of (3.90). The study also found that there is a strong correlation between transformational leadership with all of its four dimensions (idealized influence, intellectual stimulation, individualized consideration, inspirational motivation) and the effectiveness of decision-making in schools at a significance level (α≤ 0.05), which led the researcher to reject the main hypothesis of the research and its four sub-hypotheses. In the end, it was found that transformational leadership in its different dimensions offers a different interpretation and effect on the effectiveness of decision-making in schools, where the inspirational motivation (β = 1.064) came first in terms of the degree of its impact on the effectiveness of decision-making, followed by the idealized influence (β = 1.043), the individual considerations (β = 1.022), down to the intellectual stimulation (β = 1.005), all of which are statistically significant at the level of significance (α = 0.05). Finally, the study recommended the necessity of strengthening reliance on transformational leadership style in schools and educational institutions due to its great importance in making correct and effective decisions.
Keywords: Transformational leader; Decision-making; Secondary schools; Idealized influence; Intellectual stimulation; Individualized consideration; Inspirational motivation